PENGARUH PROPORSI UBI JALAR ORANYE DAN TAPIOKA TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK KERIPIK UBI JALAR ORANYE - Heveni, Enjela; Suseno, Thomas Indarto Putut; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2018)
Chips are classified as types of snacks that are categorized as crackers, foods that are dry, crisp (crispy). In general, the manufacture of chips is by way of direct material cut so many consumers who do not love because they do not obtain the desired level of crispness. It is therefore necessary to add starches such as tapioca to improve the crispiness of the chips. In this study, sweet potato being processed first and the addition of starch such as tapioca to increase the crispiness. But the addition of starch is not more than 30% by the weight of sweet potato dough for undesirable development of large volumes such as chips which are made by flour. The addition of tapioca starch will also affect the physicochemical and organoleptic properties of the chips. The study was conducted to determine the effect of tapioca proportion to the physicochemical properties and organoleptic orange sweet potato chips. The study design used is Random Group non factorial. Factors studied were concentration of tapioca which consists of 7 (seven) standard of treatment in the form of 0% (w / w); 5% (w / w); 10% (w / w); 15% (w / w); 20% (w / w); 25% (w / w); 30% (w / w), with a repeat of four (4) times in order to obtain a total of 28 experimental units. The use of the higher tapioca starch increases the water content of the raw chips, volume expansion, oil absorption and lightness, while the water content of the cooked chips, redness, yellowness, chroma and texture decreases. The results showed that the best processing is the concentration of tapioca 30% with the moisture content of 7.61% raw chips, cooked chips water content of 2.91%, volume expansion of 57.24%, oil absorption of 34.58%, texture (hardness) of 232.38 g, beta carotene of orange sweet potato flour 88.34 mg/kg, beta carotene of orange sweet potato chips after being fried 40.68 mg/kg, the acceptance level panelists in terms of the ability to fracturing (6.95), the crispness (7.33), color (7.16) and flavor (6.76) with a standard score of 1-9.